Communicating for managerial effectiveness : problems, strategies, solutions - Clampitt, Phillip G. (Sage Publications, 2010)
The Fourth Edition empowers readers to: manage information; select appropriate communication channels; develop an effective performance feedback system; communicate about organizational changes; foster interdepartmental communication and create an innovative spirit.